2004
DOI: 10.1021/op0402026
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Efficient Process for the Preparation of Sch 39166:  Aziridinium Chemistry on Scale

Abstract: A large-scale synthesis of a tricyclic D1/D5 dopamine antagonist based on regio-and stereoselective ring opening of an aziridinium ion with a Grignard reagent was optimized and scaled up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The use of the salt also removes impurities and improves the chiral purity of the reduced product. The use of sulfuric acid in sulfolane had no effect on the oxalate salt (Scheme ) …”
Section: Selected Examples Of Reactions In Sulfolanementioning
confidence: 99%
See 1 more Smart Citation
“…The use of the salt also removes impurities and improves the chiral purity of the reduced product. The use of sulfuric acid in sulfolane had no effect on the oxalate salt (Scheme ) …”
Section: Selected Examples Of Reactions In Sulfolanementioning
confidence: 99%
“…The use of sulfuric acid in sulfolane had no effect on the oxalate salt (Scheme 2). 4 In 1967 Whiting et al found that a 1:1 mixture of polyphosphoric acid (PPA) and sulfolane is a good reaction medium for the cyclization of the tetrahydronaphthol (7) to hexahydrobenzophenanthrene (8) at 125 °C for 1 h (Scheme 3). 5 Wild, et al used a 1:4.2 mixture of sulfolane and PPA to cyclize acid 9 to the dibenzocycloheptadienone (10) at 110 °C for 4 h in 24 volumes of the mixture.…”
Section: ■ Introductionmentioning
confidence: 99%
“…53 The use of b-amino alcohol 147 as the starting material for the synthesis of ecopipam is an interesting example where the rearrangement of a b-amino alcohol C was realized on an industrial scale. 54 The ecopipam precursor 150 was obtained by nucleophilic attack of the arylmagnesium bromide 149 on the benzylic position of the aziridinium 148. The rearrangement of b-amino alcohol 147 was achieved in a wide range of yields (0-84%) by activation of the hydroxy group with phosphorusbased reagents.…”
Section: R 3 = Alkylmentioning
confidence: 99%
“…The safety concerns are minimized with the use of Eaton's reagent since the resultant mixtures are more mobile solutions with temperature requirements much lower than that of PPA. Although the use of Eaton's reagent as a dehydrating agent in various reactions is well documented, Eaton's reagent-mediated cyclization of phenyl acetamide derivatives with formaldehyde was not available in the literature [7][8][9][10][11][12][13][14][15] . Cyclization of phenyl acetamides using Eaton's reagent was broadened to understand the scope and limitation of the process.…”
Section: Discussionmentioning
confidence: 99%